The impact of surgery and survival prediction in patients with bladder neuroendocrine carcinoma: a novel propensity score-matched population-based cohort study - Jianyong Liu; Shicong Lai; Na Lu; Shuhang Luo; Runhua Tang; Lin Li; Pengjie Wu; Dongwen Wang; Jun Tian (European Journal of Medical Research)
Abstract Objective To evaluate the effects of surgical interventions on individuals diagnosed with bladder neuroendocrine carcinoma (BNEC). Materials and methods Data were gathered from the Surveillance, Epidemiology, and End Results (SEER) database for this retrospective analysis. No-surgery procedures included TURBT, cryotherapy, excisional biopsy, or partial cystectomy. Surgery was categorized as cystectomy, radical cystectomy, or a more complex surgical intervention, such as exenteration. A propensity score overlap weight (PSOW) analysis was performed to adjust statistical influences between the two groups. Prognostic factors related to cancer-specific survival (CSS) and overall survival (OS) were assessed using Cox proportional hazard regression. Results A total of 2,442 participants were divided into two groups: no-surgery group (n = 1860) and surgery group (n = 582). Individuals in the no-surgery cohort showed a preference for radiation therapy (29.5% compared to 6.7%), whereas individuals in the surgery cohort were more prone to receiving chemotherapy (71.5% compared to 56.6%) as part of their treatment regimen. Surgery was determined to have a strong correlation with increased rates of OS (hazard ratio (HR) = 0.564, 95% confidence interval (CI) = 0.497–0.639, P < 0.001) and CSS (HR = 0.628, 95% CI 0.539–0.732, P < 0.001) results in BNEC patients. After PSOW, 307 patients were selected for each group. Surgical intervention demonstrated a notable enhancement in OS (P < 0.001) and CSS (P < 0.001) than those patients in the no-surgery group. Among the chemotherapy population, the median survival of patients in the surgery group was significantly higher when compared to those in the no-surgery group. Furthermore, individuals diagnosed with stage I (OS, HR = 0.202, 95% CI 0.112–0.366, P < 0.001; CSS HR = 0.198, 95% CI 0.083–0.472, P < 0.001) and II (OS HR = 0.417, 95% CI 0.331–0.525, P < 0.001; CSS HR = 0.415, 95% CI 0.307–0.561, P < 0.001) tumors who underwent surgical procedures exhibited improved long-term survival rates, whereas no surgical advantage was evident in later stages. Conclusions In the early stages of BNEC, individuals who undergo surgery experience improved survival rates. Therefore, it is important to carefully consider surgical treatment for patients with advanced BNEC.